Individual difference in configural associative learning - Byrom, N; Murphy, R (American Psychological Association, 2016)
Individuals differ in their ability to acquire associations between stimuli and paired outcomes, an ability that has been proposed to be independent of general metrics of intelligence or memory (e.g., Kaufman, DeYoung, Gray, Brown, & Mackintosh, 2009). The nature of these differences may reflect the type of associative structures acquired during learning, for instance, configuring stimuli to facilitate flexible learning and memory. We test the hypothesis that individuals differ in configural associative learning as distinct from simpler (elemental) stimulus-outcome learning. In Experiment 1 participants were screened for attentional scope and we found that attentional scope predicted configural associative learning that could not be explained simply in terms of differences in strength of associative learning. In Experiment 2, attentional scope was trained resulting in a shift in participants’ ability to learn about subsequent configurations unrelated to the training material. We discuss how the differences between individual learners reflect differences in configuring rather than simply differences in strength or speed of learning. (PsycINFO Database Record (c) 2016 APA, all rights reserved)